Neuropsychiatric changes during the COVID-19 pandemic in multiple sclerosis patients - Demir, Caner Feyzi; Bilek, Furkan; Balgetir, Ferhat (Assoc Arquivos Neuro- Psiquiatria, 2020)
Background: This study reported on a variety of psychological reactions related to anxiety, sleep quality, depression, fatigue, and quality of life in individuals with multiple sclerosis (MS), related to the Covid-19 quarantine experience. Objective: The aim of this study was to investigate the neuropsychiatric effects of the COVID-19 pandemic in MS patients and to analyze the risk factors contributing to psychological stress. Methods: The study was designed as a prospective, cross-sectional survey study. Multiple assessment tools that are used in neurological practice, including Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Fatigue Impact Scale (FIS), Pittsburgh Sleep Quality Index (PSQI), and Multiple Sclerosis Quality of Life-54 (MSQOL-54) were administered prospectively both during the early and the peak stages of COVID-19 outbreak (ESO and PSO, respectively). The survey forms were designed using SurveyMonkey and the participants were participating in the survey via a web link and QR code. Results: Fifty patients were included in the study. BDI scores, PSQI and FSI measurements, cognitive and social subscale scores and total FIS score, MSQOL-54 measurements, physical and mental subscale scores, and total MSQOL-54 score at PSO were significantly different than those at ESO. The body mass index values of the patients increased significantly at PSO compared to those measured at ESO. Conclusions: The results provide a basis for the development of psychological interventions that could minimize the prevalence of sleep disorders and depression and could improve patients' quality of life during the outbreak.
Alterações neuropsiquiátricas durante a pandemia de COVID-19 em pacientes com esclerose múltipla
Keywords: Coronavirus Infections; Pandemics; Social Isolation; Multiple Sclerosis